Cor triatriatum sinister, case report - Conde Salazar, Jose Luis (2022)
We report a case of cor triatriatum sinister associated with anomalous pulmonary venous drainage in an adult patient who presented with palpitations, lower limb edema, dyspnea, orthopnea, bendopnea and ascites. The clinical picture began with episodes of atrial fibrillation, associated with rehospitalizations for right heart failure, so angiotomography and transesophageal echography were requested, which led to the final diagnosis. The surgical approach was performed by total excision of the multifenestrating fibromuscular septum and double valvular plasty, due to severe mitral and tricuspid insufficiency, which improved the patient’s clinical condition. The importance of considering this acyanotic congenital heart disease within the differential diagnosis of the causes of right heart failure originating in the left atrium is recognized.